Detection of Avian bornavirus in multiple tissues of infected psittacine birds using real-time reverse transcription polymerase chain reaction. (March 2014) - Delnatte, Pauline; Mak, Matthew; Ojkic, Davor; Raghav, Raj; DeLay, Josepha; Smith, Dale A.
Avian bornavirus (ABV), the cause of proventricular dilation disease in psittacine birds, has been detected in multiple tissues of infected birds using immunohistochemical staining (IHC) and reverse transcription polymerase chain reaction (RT-PCR). In the current study, real-time RT-PCR, using primers targeting the ABV matrix gene, was used to detect ABV in 146 tissues from 7 ABV-infected psittacine birds. Eighty-six percent of the samples tested positive, with crossing point values ranging from 13.82 to 37.82 and a mean of 22.3. These results were compared to the findings of a previous study using gel-based RT-PCR and IHC on the same samples. The agreement between the 2 RT-PCR techniques was 91%; when tests disagreed it was because samples were negative using gel-based RT-PCR but positive on real-time RT-PCR. Agreement with IHC was 77%; 16 out of 74 samples were negative using IHC but positive on real-time RT-PCR. The results suggest that real-time RT-PCR is a more sensitive technique than gel-based RT-PCR and IHC to detect ABV in tissues. The tissues that were ranked most frequently as having a high amount of viral RNA were proventriculus, kidney, colon, cerebrum, and cerebellum. Skeletal muscle, on the other hand, was found to have a consistently low amount of viral RNA.